Peningkatan Kemampuan Menulis Teks Deskripsi Melalui Model Quantum Teaching Pada Siswa Sekolah Menengah Pertama - Herlik Jublina Ningrum; Imam Agus Basuki (PTK: Jurnal Tindakan Kelas, 2025)
The problem faced in this study is the low ability of students in writing descriptive texts. Therefore, this study aims to improve the learning outcomes of class VII D students at SMP Negeri 2 Kediri through the application of the quantum teaching learning model. The method used is Classroom Action Research (CAR) which is implemented in two cycles. The research subjects consisted of 32 class VII D students. Data collection techniques were carried out using learning outcome tests at the end of learning and observation data. The results of the study showed a significant increase in the ability to write descriptions between cycles I and II. In cycle I, there were 26 students who achieved learning mastery with a percentage of 81.25%. Meanwhile, in cycle II, all 32 students successfully achieved learning mastery, with a percentage of 100%. These findings indicate that the application of the quantum teaching learning model is effective in improving the ability of class VII D students at SMP Negeri 2 Kediri in writing descriptive texts.